Analysis of Factors Affecting Rice Farming Income in Villages Surrounding Kerinci Seblat National Park (KSNP), Pinang Belapis Subdistrict, Lebong Regency (Journal of Integrated Agribusiness, 2026)
Lowland rice farming plays an important role in supporting the rural economy, particularly in areas surrounding the Kerinci Seblat National Park (KSNP). However, farmers' income varies considerably and is influenced by various production and socio-economic factors. This study aimed to analyze the income level of lowland rice farming and identify the factors affecting farmers' income in Pinang Belapis District, Lebong Regency. Data were collected through a survey of 243 farmers and analyzed using farm income analysis and multiple linear regression (OLS). The results showed that farmers cultivating their own land earned higher income (IDR 11,814,099 per planting season) than those operating under sharecropping arrangements (IDR 5,126,502 per planting season). Partially, land area and labor wages had a positive and significant effect on farm income, while household size and fertilizer costs had a negative and significant effect. Meanwhile, farming experience and pesticide costs showed only a weak influence, whereas education level and seed costs had no significant effect on income. Simultaneously, land area, household size, education level, farming experience, seed costs, fertilizer costs, pesticide costs, and labor wages significantly affected lowland rice farming income. Therefore, increasing the income of rice farmers in areas surrounding KSNP can be achieved through optimizing cultivated land area, improving fertilizer use efficiency, and enhancing labor productivity.